1996
DOI: 10.1097/00006454-199605000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum of human immunodeficiency virus disease in children in a West African city

Abstract: Clinical syndromes associated with HIV infection in African children are difficult to recognize without access to HIV serology. Respiratory infection and malnutrition were the dominant clinical syndromes in HIV-positive children in Abidjan. Greater overlap exists between the clinical presentations of HIV-associated disease and other common health problems in African children than in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 9 publications
1
15
1
Order By: Relevance
“…Seroprevalence surveys of all paediatric admissions to major urban hospitals in Zambia and Co à te d'Ivoire have found that children with an admission diagnosis of malnutrition are more likely to be HIV-infected than children with other common admission diagnoses. 13,14 The ® nding that marasmus is particularly associated with HIV infection is also consist- ent with these earlier studies from the region. 6,10± 12 Severe wasting is a recognized feature of paediatric AIDS in African cohort studies of perinatally infected children.…”
Section: Discussionsupporting
confidence: 72%
“…Seroprevalence surveys of all paediatric admissions to major urban hospitals in Zambia and Co à te d'Ivoire have found that children with an admission diagnosis of malnutrition are more likely to be HIV-infected than children with other common admission diagnoses. 13,14 The ® nding that marasmus is particularly associated with HIV infection is also consist- ent with these earlier studies from the region. 6,10± 12 Severe wasting is a recognized feature of paediatric AIDS in African cohort studies of perinatally infected children.…”
Section: Discussionsupporting
confidence: 72%
“…64,65 Anemia prevalence among HIV-infected children varies with underlying conditions, but is usually high, ranging from 12% to 94%. [66][67][68] Moreover, anemia is a prognostic factor for negative outcomes such as progression to AIDS and early death; 66,69 thus, controlling preventable causes of anemia could also help reduce the burden of HIV-related morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…14 HIV infected children progress more rapidly than adults in the development of immune dysfunction and resultant illness by Kathleen A , et al 15 The highest incidence of AIDS occurs in the first year of life and almost all cases are due to perinatal infection.…”
Section: Frommentioning
confidence: 99%